Evaluation of Cre Recombinase Delivery in Mammalian Cells using Baculovirus Infection - Erbs, Eric (2013)
In vivo conditional knock-out of a protein is a method of choice to decipher its biological function. It can be achieved by encoding the cre-recombinase on a recombinant virus to exert spatio-temporal control of its expression and enzymatic activity and, subsequently, of the target gene deletion. Recombinant baculoviruses have been successfully used to express a wide range of proteins in insect cells. More recently, their potential to infect mammalian cells has been addressed but, so far, their ability to yield a conditional knock-out as a result of efficient in vivo cre-recombinase gene delivery has not been examined. Cre-recombinase fused to the green fluorescent protein was cloned under the control of the CAG promoter in a recombinant Autographa californica baculovirus expressing the vesicular stomatitis virus envelope G protein for increased mammalian cell infection. Gene delivery was evaluated in vitro in mammalian cells, neuroblastoma and mouse primary neuronal cultures as well as in vivo in the mouse brain. Infection with adeno-associated viruses encoding the cre-recombinase fused to the green fluorescent protein was performed as a positive control. Our results indicate that baculovirus infection leads to functional cre-recombinase expression in non-neuronal and neuroblastoma cell lines but not in mouse primary neuronal cultures or brain.